PENGHAMBATAN AKTIVITAS XANTHINE OXIDASE OLEH EKSTRAK ETANOL SARANG SEMUT (Myrmecodia tuberosa (non Jack) Bl.) SECARA IN VITRO - Ernawati Ernawati; Hari Susanti (Universitas Ahmad Dahlan, 2014)
Uric acid is the end product of purine metabolism that can settle in the joints and form small crystals, causing inflammation known as gout. Gout is a disease caused by high levels of uric acid in the blood (hyperuricemia). One of the drugs used to treat gout was allopurinol to inhibite the activity of xanthine oxidase mechanism. Myrmecodia tuberosa (non Jack) Bl. known to contain flavonoids and empirically proven to treat rheumatic complaints and gout. Therefore, research needs to examine whether the ethanol extract of the sarang semut to inhibite xanthine oxidase activity. Allopurinol is used as a comparison. The active substances of the Myrmecodia tuberosa (non Jack) Bl. was extracted with ethanol using maceration method after soaked with petroleum ether. The xanthine oxidase inhibitor activity of the Myrmecodia tuberosa (non Jack) Bl production ethanol extract was spectrophotometrically determined by monitoring the reducing of uric acid at a wavelength (λ) 295 nm with xanthine as substrate. Rate values obtained subsequently used to calculate the value of the activity. Then determined the concentration of the ethanol extract can inhibit the activity of of xanthine oxidase by 50% (IC50). The results of the research showed that the ethanol extracts of sarang semut inhibited xanthine oxidase activity with IC50 112.40 µg/ml, while allopurinol was 3.16 µg/ml.